PENGARUH KONSEP PENGUKURAN BALANCE SCORECARD TERHADAP PENGUKURAN KINERJA PERUSAHAAN JASA KONSTRUKSI PADA PT. KARSA BAYU BANGUN PERKASA DI SURAKARTA - Tarisya Ipit Puspita Sari; Sri Laksmi Pardanawati; Suhesti Ningsih (CV. Denasya Smart Publisher, 2025)
The purpose of this study was to determine the effect of the balanced scorecard concept on the measurement of the company's performance at PT. Karsa Bayu Bangun Perkasa Surakarta. This study uses a questionnaire data collection method. The population used is employee staff from all sections (Office Staff, Warehouse Section, Carpenter, and Project Logistic Section). The data analysis method is descriptive and respondents, data quality test (validity test, reliability test), classical assumption test (normality test, multicollinearity test, heteroscedasticity test) and for hypothesis testing using multiple linear analysis, F test, t test and coefficient of determination test. In this study, a sample of 100 people was obtained. Based on the test results, it can be concluded that the Financial Perspective affects Company Performance, Customer Perspective affects Company Performance, Internal Business Process Perspective affects Company Performance, and Growth and Learning Perspective affects Company Performance.